Woodworking Facilities: Driving Efficiency through Automation Applied to Major Process Steps - Gasparyan, Garik; Kunickaya, Ol'ga; Grigorev, Igor; Ivanov, Viktor; Burmistrova, Olga; Manukovskii, Andrei; Zhuk, Artem; Hertz, Edward; Kremleva, Lyudmila; Mueller, Oscar (International Journal of Engineering and Technology, 2018)
The investment scenario applied to forestry development analyzes the fundamental changes in the production structure, among other things. These changes refer to the priority development of the pulp and paper industry through the chain of large-scale woodworking facilities, where pulp, paper and cardboard manufacturing plants are the key links. Such facilities include sawmilling facilities, wood-processing factories, and timber factories. Those provide a significant economic benefit, so improving them is one of the top priorities. Considering this priority is the purpose of this article. The goal was achieved using common and scientific research methods, including mathematical modeling. Theoretical research resulted in three sets of formulas adapted for evaluating the pulpwood barking from theoretical findings on image recognition.